THE SURVEY OF NORTH BALI PRIMARY SCHOOL STUDENTS’ ATTITUDE TOWARD EFL - Pradipta, Tia Dwi (Universitas Pendidikan Ganesha, 2020)
This study aimed for investigating the primary students attitude toward EFL . The study employed a quantitative design in which the data were collected by means of a survey method. The context of the study was in one of primary schools in North Bali. The survey questionnaire was developed based on Wutz and Wedwick (2005) which shows the aspects of attitude. It can was found out that the primary students? demonstrate moderate attitude toward EFL. They were neither notably motivated nor unmotivated in learning English as a Foreign Language at school. This needs further studies to explore factors that could improve the quality of EFL classes in primary schools